Comparative evaluation of the relative efficacy of the free mucosal graft and periosteal fenestration for increasing the vestibular depth - A clinical study - Nisha Yadav; Braham Prakash Khattak; Shobhana Misra; Anamika Sharma (Wolters Kluwer Medknow Publications, 2014)
Purpose: The aim of the present study was to compare the periosteal fenestration (PF) and free mucosal graft (FMG) techniques in mandibular anterior region to increase the vestibular depth. Methodology: A total of 20 systemically healthy cases (10 patients in each group) with shallow vestibular depth and reduced width of attached gingiva in lower anterior region were included in the present study. Clinical parameters recorded included Gingival index (GI), Plaque index (PI), Oral hygiene index simplified (OHI S), Vestibular depth (VD), width of attached gingiva and post operative discomfort. Findings: The results at the end of 3 months showed that the mean GI, PI, OHI S decreased significantly and remained low throughout the study period. The mean gain in percentage of vestibular depth at the end of 3 months for group 1(PF) was 48.4% with relapse of 7.2% from the baseline. For group 2 (FMG), the mean gain in percentage of vestibular depth at the end of 3 months for was 50% with relapse of 6.2% from the baseline. The mean gain in percentage of attached gingiva at 3 months for group 1 and 2 was 65.9% and 74%, respectively. In comparison of group 1 and 2, group 2 showed better results in terms of increasing the vestibular depth and attached gingiva than group 1 although the intergroup comparison was not statistically significant. Conclusion: When aim of the clinician is to treat a patient with shallow vestibule together with reduced width of attached gingiva, the use of periosteal fenestration yields similar results to that of FMG.